Effizienz der Methode Lernen durch Lehren (LdL) – Ergebnisse eines Experiments - Janicka, Monika (Glottodidactica, 2019)
Constructivist learning approaches emphasize the interface of learning by doing and student participation, as well as the efficiency of the learning process. Research findings have also demonstrated that students learn more effectively from each other (Hattie 2013). The aim of the experiment conducted was to verify the efficiency of the “learning through teaching” method (LTT) (Martin 1985), in which students assume some of the teacher’s tasks. The experiment was conducted during the third semester of the “grammar in communication” course at the faculty of Applied Linguistics at Maria Curie-Skłodowska University. The result confirmed that, after a semester, the group working with the learning through teaching method had higher achievements than the control group. Thanks to a qualitative survey, some prospects and limits of the method could be determined. It also provided feedback for intern, process-oriented evaluation, which makes it possible to optimize course design in the future.